Kadar Hb dan Perubahan Berat Badan Tikus Wistar Model Anemia Defisiensi Besi Setelah Pemberian Minyak Ikan Patin - Hersanti Sulistyaningrum; - Sulistyaningrum (Universitas Muhammadiyah Semarang, 2022)
Anemia is a health problem with little progress in its management, even thoughthe global prevalence of anemia is relatively high. Anemia due to iron deficiency affectsweight gain in children. Giving catfish oil to anemic rats was done to see the effect onHb levels and body weight.This research is a true experiment with a randomized pre-post-test design witha control group. Male Wistar rats were divided into four groups, namely K- (rats fedstandard), K+ (rats fed standard without iron), P1 (rats fed standard without iron,getting catfish oil 0.039 ml/day), P2 (rats fed standard without iron, supplemented withferrous sulfate 0.126 mg/day) for 14 days. Hb levels were measured before and aftertreatment using the ELISA method. The rats were weighed every day.Paired t-test was conducted to determine differences in Hb levels and changesin body weight before and after the intervention. In addition, the Anova test followedby Post Hoc Bonferroni was carried out to analyze the difference in effect on the fourgroups.There were significant differences in body weight changes before treatment and aftertreatment (p=0.00, p<0.05) on K-(13 gram ± 0.81), K+(5.5 gram ± 1.04), P1 (12 grams± 0.7), P2 (13 grams ± 0.63). In addition, the study showed a significant increase inHb levels before and after treatment (p=0.00, p<0.05) at P1(4.7 g/dL ± 0.76) andP2(5.13 g/dL ± 0.15 ), as well as a decrease in K- (0.09 g/dL ± 0.19) and K+ (0.37g/dL ± 0.18).There was an effect of giving catfish oil on Hb levels and changes in bodyweight, which increased significantly in iron deficiency anemia Wistar rats.Keyword: body weight, catfish oil, Hb levels iron deficiency anemia